2021
DOI: 10.1108/jamr-01-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between work–life balance and job satisfaction: moderating role of training and development and work environment

Abstract: PurposeThe purpose of this study is to investigate the relationship between work–life balance (WLB) and job stress, job commitment and job satisfaction. Further, the role of work environment and training and development as moderators in the relationship between WLB and its consequences is investigated.Design/methodology/approachUsing a structured survey instrument, this paper gathered data from 331 respondents working in a transportation company in southern part of India. After checking the psychometric proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 97 publications
3
15
1
2
Order By: Relevance
“…As several studies found that communication (vertical, horizontal and downward) plays a vital role in enhancing productivity and performance, our results are not surprising. Third, this study found that WLB is significantly and positively associated with performance (hypothesis 3), which supports the findings from the literature (Aruldoss et al. , 2022; Huang et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As several studies found that communication (vertical, horizontal and downward) plays a vital role in enhancing productivity and performance, our results are not surprising. Third, this study found that WLB is significantly and positively associated with performance (hypothesis 3), which supports the findings from the literature (Aruldoss et al. , 2022; Huang et al.…”
Section: Discussionsupporting
confidence: 91%
“…, 2001, p. 49). Literature search reveals that some researchers see WLB in terms of minimizing conflict between work and non-work, whereas others see it in terms of effectiveness and satisfaction (Aruldoss et al. , 2022; Casper et al.…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the moderating effect of T&D on the relationship between CD and ER, our finding is similar to Imna and Hassan (2015) but contradicts some studies, such as Kodwani and Prashar (2019), Abdulhabib and Al-Dhaafri (2019) and Aruldoss et al (2021), who found T&D has a significant moderating effect on the relationship between CD and employee outcomes, such as innovation, commitment, and performance. Therefore, H7 could not be supported.…”
Section: Discussioncontrasting
confidence: 83%
“…Similarly, T&D had a positive and significant moderating effect on the relationship between foreign technology licencing and innovation (Nguyen-Van & Chang, 2020). Another study showed that T&D significantly moderated the relationship between talent management and job satisfaction (Aruldoss, Kowalski, Travis, & Parayitam, 2021). They also found that serviceoriented training moderated the relationship between talent management and organizational commitments (Aruldoss et al, 2020), such as employee turnover intention.…”
Section: Moderating Effects Of Training and Developmentmentioning
confidence: 96%